Charting the Territory: Recombination as a Source of Uncertainty for Potential Entrants - Montauti, Martina; Wezel, Filippo Carlo (Organization Science, 2016)
In this paper, we conceptualize categories as regions of a cognitive map that structure the market and guide the investment decisions of potential entrants—i.e., of new and established organizations. We advance that, as a category appears altered via incumbents’ acts of recombination, potential entrants face market-specific uncertainty and are discouraged to invest in that category. These negative effects of recombination on market entries are, however, mitigated at increasing values of category status. We test our arguments in the market for electronic music. The analyses of product and organizational entries in music styles between 1978 and 2011 lend support to our arguments.